Diastereoisomer-Specific Biotransformation of Hexabromocyclododecanes by a Mixed Culture Containing Dehalococcoides mccartyi Strain 195 - Zhong, Yin; Wang, Heli; Yu, Zhiqiang; Geng, Xinhua; Chen, Chengyu; Li, Dan; Zhu, Xifen; Zhen, Huajun; Huang, Weilin; Fennell, Donna E.; Young, Lily Y.; Peng, Ping’an (Frontiers in Microbiology, 2018)
Hexabromocyclododecane (HBCD) stereoisomers may exhibit substantial differences in physicochemical, biological and toxicological properties. However, there remains a lack of knowledge about stereoisomer-specific toxicity, metabolism, and environmental fate of HBCD. In this study, the biotransformation of (±)α-, (±)β-, and (±)γ-HBCD contained in technical HBCD by a mixed culture containing the organohalide-respiring bacterium Dehalococcoides mccartyi strain 195 was investigated. Results showed that the mixed culture was able to efficiently biotransform the technical HBCD mixture, with 75% of the initial HBCD (~ 12 μM) in the growth medium being removed within 42 days. Based on the metabolites analysis, HBCD might be sequentially debrominated via dibromoelimination reaction to form tetrabromocyclododecene, dibromocyclododecadiene, and 1,5,9-cyclododecatriene. The biotransformation of the technical HBCD was likely diastereoisomer-specific. The transformation rates of α-, β- and γ-HBCD were in the following order: α-HBCD > β-HBCD > γ-HBCD. The enantiomer fractions of (±)α-, (±)β- and (±)γ-HBCD were maintained at about 0.5 during the 28 days of incubation, indicating a lack of enantio-selective biotransformation of these diastereoisomers. Additionally, the amendment of another halogenated substrate tetrachloroethene (PCE), which supports the growth of strain 195, had a negligible impact on the transformation patterns of HBCD diastereoisomers and enantiomers. This study provided new insights into the stereoisomer-specific transformation patterns of HBCD by anaerobic microbes and has important implications for microbial remediation of anoxic environments contaminated by HBCD using the mixed culture containing Dehalococcoides.